Surface hardness of composite resins After the contact with siwak stem infusion - Soebagio,; Yogiartono, R. Moh. (International Journal of Psychosocial Rehabilitation, 2020)
Background: Composite resins have hydrophilic properties so they can absorb water and chemical substances from the surrounding environment and can remove the components contained in the composite resin itself (deleterious effects). This effect can be in the form of volume changes such as enlargement, physical changes such as plasticization and softening, as well as chemical changes such as oxidation and hydrolysis. Purpose: To analyze the hardness of composite resin after contact with siwak stem infusion. Method: This type of research is a laboratory experimental study with before after research design. Analysis done using the normality test with Kolmogorov-Smimov. Result : There is a decrease in hardness every time. At the 1 hour immersion the composite resin hardness averaged at 82.2200 Hv. In the 2 hour immersion the average hardness decreased to 77.7400 Hv, and in the 3 hour immersion the hardness of the resin decreased again with an average hardness of 69.1800 Hv. Conclusion : In this study composite resin samples continued to decrease from 1 hour, 2 hours and 3 hours.